2018
DOI: 10.3368/jhr.55.3.0417-8752r2
|View full text |Cite
|
Sign up to set email alerts
|

Are Professors Worth It?

Abstract: A substantial share of university instruction happens in tutorial sessionssmall group instruction given parallel to lectures. In this paper, we study whether instructors with a higher academic rank teach tutorials more effectively in a setting where students are randomly assigned to tutorial groups. We find this to be largely not the case. Academic rank is unrelated to students' current and future performance and only weakly positively related to students' course evaluations. Building on these results, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Pounder (2014) argues that teachers displaying transformational classroom leadership behaviours stimulate academic motivation and effort, engage students in instructional activities in their own time, engender self-efficacy and facilitate cognitive and affective learning. Ran and Xu (2019) and Feld et al (2020) analyse how various teacher characteristics impact student learning outcomes and student performance. One way that teacher performance is influential is through the emotions of students, as Goetz et al (2013) showed, for example, that a supportive presentation style was conducive to students exhibiting positive emotions like enjoyment and pride, while high levels of excessive demand from lessons were associated with negative emotions like anxiety, anger and helplessness.…”
Section: Introductionmentioning
confidence: 99%
“…Pounder (2014) argues that teachers displaying transformational classroom leadership behaviours stimulate academic motivation and effort, engage students in instructional activities in their own time, engender self-efficacy and facilitate cognitive and affective learning. Ran and Xu (2019) and Feld et al (2020) analyse how various teacher characteristics impact student learning outcomes and student performance. One way that teacher performance is influential is through the emotions of students, as Goetz et al (2013) showed, for example, that a supportive presentation style was conducive to students exhibiting positive emotions like enjoyment and pride, while high levels of excessive demand from lessons were associated with negative emotions like anxiety, anger and helplessness.…”
Section: Introductionmentioning
confidence: 99%
“…As we discuss below, we believe that the effect of TAs is unlikely to be consistent with the overall pattern of our findings. Previous research on the role of TAs suggest that they are unconnected with students' future academic outcomes (Feld et al, 2020). Moreover, we believe that using within cohort peer group randomization is an improvement over studies using between cohort comparisons.…”
Section: Summary Statisticsmentioning
confidence: 80%
“…Note that, since students were assigned randomly conditionally on gender, age and Danish citizenship, we always compare pairs of students conditioning on these covariates 18. Previous research suggests that instructors with higher academic rank are unrelated with students' future academic outcomes(Feld et al, 2020) 19. We believe that using within cohort peer group randomization is an improvement over studies using between cohort comparisons.…”
mentioning
confidence: 99%